Divine Comedies for the New Millennium Recent Dante Translations in America and the Netherlands - de Rooy, Ronald (Amsterdam University Press, 2003)
Dante's intranslatability paradoxically causes a steady flux of translations, overwhelming in America, much more modest in the Netherlands. However, the tiny Netherlands witnessed a remarkable boom of Dante translations around the year 2000: within a short period seven cantiche were translated by Dutchmen and seven by Americans. This historic moment gave rise to a seminar about these recent translations, and about the traditions of translating Dante in both nations. The American and Dutch Divine Comedies discussed in this volume are important landmarks in a long tradition of making Dante's work accessible to non-Italian readers in both countries. On this already crowded stage, however, every newcomer inevitably makes statements about how Dante's masterpiece should be read: as a poem, as a scholarly text or as a scholarly poem? The old polarization between the fearless (at times reckless) 'poetical' translators and the more cautious 'academic' translators is very much alive, and the choice seems one between compromise and confrontation, between caution and courage.